«¡España viva!»: Personifications of Spain in Lope de Vega's «comedias de santos» - Roy Norton (Universitat Autònoma de Barcelona, 2017)
This study concerns the personification España as she appears, briefly, in four saints plays by Lope de Vega. It presents an analysis of her function, character, and likely appearance. It argues that Lope deploys España –in the majority of cases in commissioned plays forming part of public festivals of national significance– to advocate the hispanicization of the lives of non-Spanish saints and of universal Catholic dogma. The essay argues further that, influenced by the iconographic and emblematic traditions, España is characterized by Lope as courteous and genteel at home, but feisty and belligerent when faced with foreign adversaries, her appearance on stage probably reflecting aspects of that character.